2020
DOI: 10.3390/nano10112171
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Blue-Emissive InP/GaP/ZnS Quantum Dots via Controlling the Reaction Kinetics of Shell Growth and Length of Capping Ligands

Abstract: The development of blue-emissive InP quantum dots (QDs) still lags behind that of the red and green QDs because of the difficulty in controlling the reactivity of the small InP core. In this study, the reaction kinetics of the ZnS shell was controlled by varying the length of the hydrocarbon chain in alkanethiols for the synthesis of the small InP core. The reactive alkanethiol with a short hydrocarbon chain forms the ZnS shell rapidly and prevents the growth of the InP core, thus reducing the emission wavelen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In line with the growth of a sulfur rich Zn(Se,S) 10,90 shell, the diffraction pattern of these cyan/blue emitting QDs nearly coincides with that of ZnS, see Figure 8c. So far, only few studies have reported the formation of cyan/blue InP-based QDs, 28,29,42,43 with highest PLQYs reported so far of 70% at a peak emission wavelength of 490 nm and a line width of 48 nm. 28 Similarly, we explored adaptations to the initial red QD synthesis protocol to synthesize amber-emitting InP-based QDs.…”
Section: Resultsmentioning
confidence: 99%
“…In line with the growth of a sulfur rich Zn(Se,S) 10,90 shell, the diffraction pattern of these cyan/blue emitting QDs nearly coincides with that of ZnS, see Figure 8c. So far, only few studies have reported the formation of cyan/blue InP-based QDs, 28,29,42,43 with highest PLQYs reported so far of 70% at a peak emission wavelength of 490 nm and a line width of 48 nm. 28 Similarly, we explored adaptations to the initial red QD synthesis protocol to synthesize amber-emitting InP-based QDs.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure a and Table S1, when the temperature was not maintained, the FWHM of QDs increases gradually with the increase of injection temperature, and PL redshift is associated with the increase of temperature above 110 °C. Based on the typical method (30 °C, 0 min), , we can obtain the QDs with a PL peak of 484 nm and FWHM of 48 nm. After they were maintained for 20 min at the corresponding temperature, the samples below 110 °C showed no significant difference, while all the samples above 110 °C showed different degrees of FWHM narrowing.…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier study, wide-band gap ZnS epitaxy directly on the InP core was implemented, but the lattice mismatch of InP-ZnS resulted in the unexpected interface defects, which prevented the formation of a perfect heteroepitaxial interface without defects and limited the thickness of an epitaxial shell. Most recently, an intermediate buffer layer with a lattice constant close to those of InP and ZnS (e.g., ZnSe, ,,, ZnSeS, and GaP ,, ) has been used to reduce lattice mismatch between the core and shell. Because the ZnSe shell inevitably causes large red shift of emission, the GaP intermediate shell is widely used in blue-emitting InP QDs.…”
Section: Introductionmentioning
confidence: 99%
“…However, their work required a significantly complex preparation process, such as various state precursors (solid and gas states), or an extremely careful step-by-step protocol for uniform and high-quality colloidal QDs. Accordingly, for commercialization, a simpler and more economic method for synthesis should be developed [ 17 ].…”
Section: Introductionmentioning
confidence: 99%